Comparison of methods for proanthocyanidin extraction from pine (Pinus densiflora) needles and biological activities of the extracts - Kim, Nam-Young (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2010)
Flavonoids are known to be effective scavengers of free radicals. In particular, proanthocyanidins are flavonoids that possess cardiovascular protection, antioxidative activities, and immunomodulatory activities. Here, we evaluated proanthocyanidin contents in the total polyphenolic compounds of pine needle extracts prepared by hot water, ethanol, hexane, hot water-hexane (HWH), and hot water-ethanol (HWE). Analysis of each extract indicated that the ethanol extract contained the highest proanthocyanidin concentration. The HWH and hexane extracts also contained relatively high concentrations of proanthocyanidin. On the other hand, proanthocyanidin content analyses out of the total polyphenolic compounds indicated that the HWH extract contained the highest content. These results suggest that HWH extraction is a suitable method to obtain an extract with a high level of pure proanthocyanidins and a relatively high yield. The HWH extract possessed superior activity in diverse antioxidative analyses such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferrous ion chelating (FIC), and ferric-ion reducing power (FRAP) assays. In addition, upon assessing the effects of the pine needle extracts on macrophages (Raw 264.7 cell), the HWH extract exhibited the highest activity. In this study, we discerned an efficient extraction method to achieve relatively pure proanthocyanidins from pine needles and evaluated the biological functions of the resulting extract, which could potentially be used for its efficacious components in functional food products.